A Megabase-Scale Deletion is Associated with Phenotypic Variation of Multiple Traits in Maize. Issue 1 (1st November 2018) - Han, Xuesong; Qin, Yao; Yu, Feng; Ren, Xuemei; Zhang, Zuxin; Qiu, Fazhan
Abstract: Genomic deletions are pervasive in the maize ( Zea mays L.) genome, and play important roles in phenotypic variation and adaptive evolution. However, little is known about the biological functions of these genomic deletions. Here, we report the biological function of a megabase-scale deletion, which we identified by position-based cloning of the multi-trait weakened ( muw ) mutant, which is inherited as a single recessive locus. MUW was mapped to a 5.16-Mb region on chromosome 2. The 5.16-Mb deletion in the muw mutant led to the loss of 48 genes and was responsible for a set of phenotypic abnormities, including wilting leaves, poor yield performance, reduced plant height, increased stomatal density, and rapid water loss. While muw appears to have resulted from double-stranded break repair that was not dependent on intragenomic DNA homology, extensive duplication of maize genes may have mitigated its effects and facilitated its survival.